The Effect Of Earning Rate And Tax Sanctions On Taxpayers’ Compliance In Reporting Tax Annual Letter Of Notification For Private Taxpayers In The Area Of Medan Deli - Novien Rialdy (AIBPM Publisher, 2020)
Medan Deli describes one of the districts in the city of Medan which is included in the authority of the Tax Office (KPP) Pratama Medan Belawan. Taxpayer compliance particularly individuals is still very low in the area of Medan Belawan. There are several aspects that affect the taxpayer compliance level, including the level of income tax payers and tax penalties. There are three theories used in this study including theories about the level of income, the theory of tax penalties and theory of taxpayer compliance. This research methods used in this study are quantitative approaches, type of exposure studies and the nature of study explanatory. The study populations were all individual taxpayers in Medan Deli district, amounting to 25. 650 taxpayers. The samples were 100 taxpayers. The study showed that the level of earnings and tax penalty simultaneously affected taxpayers compliance as shown by F-observed (132,033) > F-table (3,09) and partially earning level affected taxpayers’ compliance in which F-observed (4,744) > F-table (1,98472), and partially tax penalty affected taxpayers’ compliance in which t-observed ((3,770) > t-table (1,98472). This study concluded that the level of income and the tax penalty affect tax compliance in submitting the annual letter of notification (SPT) for individual taxpayers in Medan Deli area.